Tolosa-Hunt syndrome in pediatric practice - E.V. Shishkina; T.N. Bazilevskaya; R.F. Izokhvatova; I.V. Novikova; Yu.V. Panfilova; M.Yu. Galaktionova; D.A. Maiseenko (РМЖ. Мать и дитя, 2020)
E.V. Shishkina1, T.N. Bazilevskaya2, R.F. Izokhvatova2, I.V. Novikova2, Yu.V. Panfilova2, M.Yu. Galaktionova1, D.A. Maiseenko1 1Prof. V.F. Voino-Yasenetsky Krasnoyarsk State Medical University, Krasnoyarsk, Russian Federation 2Krasnoyarsk Interregional Children’s Clinical Hospital, Krasnoyarsk, Russian Federation Tolosa-Hunt syndrome (THS) is a rare disease manifested with one or more cranial nerve disorders and orbital pain. In children, THS is diagnosed very rarely due to the lack of vigilance among physicians. Careful examination including MRI or helical CT help diagnose this disease. This paper discusses case history of THS in a child in the first ten years of life who has previously experienced similar episodes of ptosis and right-sided orbital pain; however, the cause of these symptoms has remained elusive. Disease anamnesis, clinical signs, neurological status, and additional diagnostic data are described in detail. Clinical course of THS with its relapses and remissions, rapid symptom regress after corticosteroid pulse therapy, and no specific granulomatous inflammation of the lateral wall of the cavernous sinus as demonstrated by MRI suggest idiopathic THS. The importance of in-depth neurological and general examination of patients with clinical signs of THS due to a variety o f the causes of this syndrome is highlighted. Keywords: pediatrics, Tolosa-Hunt syndrome, ophthalmoplegia, superior orbital fissure, cavernous sinus, corticosteroids. For citation: Shishkina E.V., Bazilevskaya T.N., Izokhvatova R.F. et al. Tolosa-Hunt syndrome in pediatric practice. Russian Journal of Woman and Child Health. 2020;3(4):336–339. DOI: 10.32364/2618-8430-2020-3-4-336-339.